Knowledge workers: empowering organization's competitive advantage/ Mohd Firdaus Mohd Helmi ... [et al.] - Mohd Helmi, Mohd Firdaus; Mustaffar, Mohd Yusof; Hashim, Nurhidayah (Faculty of Information Management, Universiti Teknologi MARA, 2014)
In knowledge age, wealth is based on who owns the knowledge and how it is utilized to create goods and services that improve the global economy. Today's knowledge capital is the most valuable assets compared with the physical assets. Thus, in order to compete in a highly competitive economy, called "Knowledge Economy." organizations need to think and act differently. Organizations need an enabler that can help them ahead from others which is the new generation of workers known as "Knowledge Workers. 11 Knowledge workers are proven to be a critical success factor in helping the organizations to improve their competitive advantage. However, organizations need to be aware that this type of workers are highly mobile which means, if they feel their needs are not fulfilled or appreciated they will move to another organization and bring their valuable tacit knowledge as well. It is important to ensure these employees are retained as long as their knowledge is valuable to the organizations and motivate them to remain in the organizations.